Developing a minimal-input one-dimensional methodology for modelling axial compressors using a diffuser analogy - Barlin, Daniel (Department of Mechanical Engineering, 2024)
Despite notable advances in Computational Fluid Dynamics as a tool for gas turbine design, the analysis and performance prediction of turbomachinery still benefits greatly from the use of one- dimensional mean-line modelling, as it can provide results of acceptable accuracy while requiring fewer geometric inputs, as well as comparatively lower computational expenses. However, even mean-line codes are often limited by the amount of geometric and operational data available, often withheld by Original Equipment Manufacturers for proprietary reasons. As a result, a large number of tuning factors are often employed in mean-line simulations to achieve more accurate results. This report describes the development of a one-dimensional modelling methodology which requires minimal geometric inputs and tuning factors for predicting the performance of a transonic axial compressor stage, for use in a gas turbine. The minimal input model is achieved through development of a diffuser analogy, whereby the stage's rotor and stator rows are modelled as simple diffusers with passage flow areas approximately equal to those in the compressor stage. A design point calibration operation is first performed to estimate all diffuser flow path areas using a set of industry knowledge-based assumptions, and blade angles are determined using widely adopted correlations from open literature. The estimated geometries are then used as inputs for an off-design model built in Flownex SE. Using correlations of total pressure loss from the open literature, the Flownex model is then able to predict the stage's performance over a range of off-design operating conditions. The model was validated against a well-documented axial compressor stage from NASA through four successive models. First, Flownex's built-in Designer function was used to determine the rotor losses that would result in good agreement with experimental data of stage total pressure ratio. The second model adopted a simple total pressure loss correlation from the literature. The third model employed a single calibration factor for adjusting flow path areas, in order to obtain better agreement with the experimental data. Further definition of the area calibration factor was achieved by applying the third model to three other NASA compressor stages. Finally, correlations determined from this exercise were evaluated. The methodology presented an efficient means of predicting compressor stage performance with acceptable accuracy, while requiring minimal geometric inputs and only a single calibration factor, thus allowing gas turbine operators and analysts to gain greater insight into the compressor's off-design behaviour with the limited geometric and operational data available to them.